Telemedicine and Telehealth in Urology: Uptake, Impact and Barriers to Clinical Adoption - Naik, Nithesh; Nandyal, Shreyas Raghavan; Nayak, Sanjana Ganesh; Shah, Milap; Ibrahim, Sufyan; Hameed, B. M. Zeeshan; Patil, Ananth; Suresh, Gopika; Shetty, Pritam A.; Rai, Bhavan Prasad; TP, Rajeev; Rice, Patrick; et al. (Frontiers in Surgery, 2022)
Telemedicine has great potential in urology as a strong medium for providing patients with continuous high-quality urological care despite the hurdles involved in its implementation. Both clinicians and patients are crucial factors in determining the success of tele-consults in terms of simplicity of use and overall satisfaction. For it to be successfully incorporated into routine urological practice, rigorous training and evidence-based recommendations are lacking. If these issues are addressed, they can provide a significant impetus for future tele-consults in urology and their successful deployment, even beyond the pandemic, to assure safer and more environment-friendly patient management.